Scandal and religious identity in early Stuart England : a Northamptonshire maid's tragedy - Lake, Peter; Stephens, Isaac (Studies in modern British religious history, 2015)
A window into the mental and cultural worlds of the Stuart period, capturing the existing religious, social and political tensions on the eve of the English Civil War.